Hello every one I have this vector relation E=A+(HXA) where E,A and H are vectors I want to proof that A=(E-(HXA))/
any one remeber how we can do this using vector identities or simple geometry or both of them (may be)?
Hello every one I have this vector relation E=A+(HXA) where E,A and H are vectors I want to proof that A=(E-(HXA))/
any one remeber how we can do this using vector identities or simple geometry or both of them (may be)?
As stated this is not true.
It is true that .
Because H is a vector has no meaning.